ANALISIS PREDIKSI KEBANGKRUTAN PERUSAHAAN PUBLIK DI INDONESIA - Winny Lian Seventeen (Jurnal Ilmu Akuntansi, 2019)
This study aimed to analyze the bankruptcy prediction public companies in Indonesia, The population in this study is a bankrupt company to ever be listed on the Stock Exchange in 1998-2015 and similar companies for comparison. This type of research used in this research is descriptive research with quantitative approach. The samples selected 42 enterprise units of analysis. Tools of data analysis in this study using Altman Z "-Score modificated and Springate S-Score. The results from each model in the count back using logistic regression to see the best model in predicting bankruptcy. The results of this study indicate that the Altman Z "-Score modificated and Springate S-Score, none of the models in this study can be used to predict the bankruptcy of public companies in Indonesia.